Hypertrophic pachymeningitis and encephalitis in a patient with relapsing polychondritis. Issue 1 (17th November 2014) - Nakamura, Ken; Sugaya, Keizo; Nakata, Yasuhiro; Shima, Sayuri; Mutoh, Tatsuro; Nakano, Imaharu
Abstract Relapsing polychondritis is a rare autoimmune multisystem disease characterized by the inflammation of cartilaginous tissues. Neurological complications with relapsing polychondritis are extremely rare. We report an 81‐year‐old woman with relapsing polychondritis who subsequently developed encephalitis and cognitive impairment. Brain magnetic resonance imaging showed slightly high signal intensity in the bilateral frontal dura mater using fluid‐attenuated inversion recovery. T1‐weighted images with contrast enhancement showed abnormal enhancement of the dura mater, indicating hypertrophic pachymeningitis. To our knowledge, this is the first case report of relapsing polychondritis complicated by both hypertrophic pachymeningitis and encephalitis in the absence of other recognizable autoimmune diseases.